Pendampingan Petani dalam Pengendalian Hama dan Penyakit Jambu Biji (Psidium guajava L.) di Desa Cibening, Kecamatan Pamijahan, Bogor, Jawa Barat - Ruomenson Dedi Jefri Bakara; Fitrianingrum Kurniawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The majority of people in Cibening, Sub-district Pamijahan work as farmers. Guava is the main commodity that has been cultivated. This village is also a contributor to Bogor Regency, which is the third largest guava producer in West Java province. However lately the production of guava in this area has decreased so that farmers suffered significant losses. This loss caused by a pest attack that occurs for a long time. The main pest and disease in this village are Helopeltis sp. and plant parasitic nematodes. Farmers in this village still do not understand in detail related how to manage pest and disease. The use of chemical pesticides is the only one control strategy for pest and disease. With these conditions, farmers need assistance to solve the problem. This activity was done through three stages, namely preliminary survey, socialization related to the introduction and control of pests and diseases of guava, and training of PGPR as a biological agent and planting Tagetes sp as refugia and nematicidal actvity. The ojective of this activity was to enable farmers to have the ability to solve pest and disease problems damaging guava, with proper control that takes into account all aspects, so farmers get more financial benefits and environmental sustainability in this village can be realized. Guava farmers in Cibening Village, Pamijahan are able to recognize and deal with pests and diseases that attack guava independently and farmers get more financial and environmental sustainability benefits.